The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/13691050801915184
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual experiences of secondary school pupils in Ireland: sexual coercion in context

Abstract: This article reports on data from a wider study on adolescent sexuality in Ireland and focuses particularly on the topic of heterosexual experiences and how these experiences relate to sexual coercion. Data were gathered from 29 focus group interviews with 102 young women and 124 young men, and were analysed using a qualitative research strategy. Drawing on the concepts of social coercion and interpersonal coercion first introduced by Finkelhor and Yllo (1983), we argue that both female and male participants r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…, Hyde et al . ,b, , Suvivuo et al . , Barrientos Delgado & Silva Segovia , Lesch & Furphy , Chang et al .…”
Section: Resultsunclassified
“…, Hyde et al . ,b, , Suvivuo et al . , Barrientos Delgado & Silva Segovia , Lesch & Furphy , Chang et al .…”
Section: Resultsunclassified
“…Sexual coercion in adolescence is a recurring theme in the literature [6,11,14,15,16], with the figure reported by young women higher than that reported in a UK study in which approximately a quarter of the young women interviewed referred to sexual violence or various types of pressure to have sex against their wishes [17].…”
Section: Discussionmentioning
confidence: 99%
“…(Aspects of the wider study are published elsewhere [9,10,11,12,13]). In the wider study, 29 focus group interviews were conducted with 226 secondary school pupils (102 females and 124 males) in Ireland during 2003-4, and after each focus group, participants were invited to fill out a short anonymous questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…While much of the feminist research and theorizing on heterosexual violence has interrogated the role of gender norms (DeKeseredy & Kelly, 1993;Hyde et al, 2008;Impett & Peplau, 2003;Impettet al, 2006;LaCasse & Mendelson, 2007;Maxwell et al, 2003;Miller et al, 2007;Mercer, 1988;Morgan & Zurbriggen, 2007), their relationship to adolescent girls' experiences of sexual victimization remains unclear. One study found that males who accepted rape myths were significantly more likely to perpetrate violence.…”
Section: Gender Ideologiesmentioning
confidence: 99%
“…Considering the interrelationships between social and interpersonal coercion and unwanted sexual experiences (USEs), Hyde, Drennan, Howlett, and Brady (2008) conceptualize social coercion, heterosexual norms, and discourses as indirect pressure;…”
Section: Sexual Violencementioning
confidence: 99%